Perancangan alat Penyiram Jagung Portabel Semi-Otomatis dalam Mendukung Pertanian Jagung Modern - Septiani, Riana; Sundari, Susanti; Hidayat, Ghapur; Pratama, Aam Wahyu (Fakultas Teknik Universitas Tulang Bawang, 2024)
Corn farmers generally maintain corn plants by watering them with fertilizer or pesticides which is usually done with a device available on the market in the form of a tube connected by a hose to a spray stick to spray the solution onto the plants. Standard factory spray equipment on the market is difficult to use, ineffective and also inefficient. The use of a carrying sprayer is less effective in reaching corn plants that are almost the same as an adult's height, and human power still plays a very big role. The aim of this research is to make improvements to the design of spray equipment to correct the shortcomings of existing spray equipment. The French method used in this research is based on the effectiveness of this method in meeting data needs comprehensively when designing new products, it is very flexible and can be adapted to various types of products. This research succeeded in creating a design and prototype for a semi-automatic portable corn sprinkler. The state of the art from this research is that the design of this plant sprayer can be disassembled and installed to suit the size of the land and is very flexible, which is designed to support regional and national government programs for the welfare of corn farmers. The land area that can be watered by the new tool is wider, namely 200 m2 x 4 with a time of 2 hours; Meanwhile, the tools sold on the market are still manual and can only water an area of ​​200 m2 x 2 for 4 hours. Keywords: Corn plants ;Design ; Portable ; Sprayer